2010
DOI: 10.1152/ajprenal.00451.2009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Notch activation on the regenerative response to acute renal failure

Abstract: Episodes of acute renal failure (ARF) are not always fully reversible and may lead to chronic disease, due in part to an inadequate regenerative response. The Notch signaling pathway is involved in determining cell fate during development, and tissue maintenance and repair in adult organs. The purpose of this study was to examine the role of the Notch pathway in renal regeneration following ARF. Kidney injury, induced by ischemia-reperfusion, resulted in early activation of the Notch pathway, as evidenced by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 65 publications
1
40
0
Order By: Relevance
“…The early improvement in renal function has been reported in other forms of cytotherapy of AKI (23,24), and this early effect has been cited as reflecting a paracrine action (10). The early activity achieved by cell transfer is clearly desirable, for it is more likely to limit renal damage and subsequent progression to chronic renal failure (8,18). The improved renal function was not derived from improved microvascular flow, which remained unmodified by cell transplantation, in agreement with prior reports derived in another cell transfer system (26).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The early improvement in renal function has been reported in other forms of cytotherapy of AKI (23,24), and this early effect has been cited as reflecting a paracrine action (10). The early activity achieved by cell transfer is clearly desirable, for it is more likely to limit renal damage and subsequent progression to chronic renal failure (8,18). The improved renal function was not derived from improved microvascular flow, which remained unmodified by cell transplantation, in agreement with prior reports derived in another cell transfer system (26).…”
Section: Discussionmentioning
confidence: 94%
“…More recent comparative work on AKI and renal ontogeny has uncovered shared mechanisms for reparative tubulogenesis and embryonic tubulogenesis (5,27). Accordingly, factors that participate in kidney development have also being tested on AKI, including bone morphogenetic protein (28), glial cell line-derived neutrophic growth factor (25), and notch pathway ligand DLL4 (8). Current work has demonstrated a strong renal inflammatory component following AKI (14), and some have reported that mediators of inflammation could also be beneficial in AKI (4).…”
mentioning
confidence: 99%
“…There are several examples of developmental signaling pathways that are reactivated in the adult descendants of progenitor cells during injury. Fibroblast growth factor-7, 54 the notch pathway, 55 and Gli1 re-expression 1 are examples of developmental pathways being reactivated during injury in the adult. Wnt4 is expressed in epithelial progenitors during development and is required for tubulogenesis, and Wnt4 is also expressed developmentally in medullary stroma.…”
Section: Discussionmentioning
confidence: 99%
“…The Notch pathway-regulated gene expression occurs in both developing and adult kidneys, and Notch signaling pathways are activated in the adult kidney after injury. 10 Recent studies have documented that Hes protein induced by activation of Notch receptor signaling pathways may function as a nonreceptor scaffold protein in the nucleus that can recruit and allow Janus kinase 2 (JAK2) to phosphorylate signal transducers and activators of transcription 3 (STAT3), thereby leading to activation of an STAT3 signaling pathway. 11 Survivin, which is the smallest member of the inhibitor of apoptosis proteins family, is a 16.5 kDa intracellular protein that has been implicated in regulation of apoptosis, cell division, and cell cycle in cancer cells as well as normal tissues through caspasedependent and -independent mechanisms.…”
mentioning
confidence: 99%